Voice from the north : resurrecting regional identity through the life and work of Yi Sihang (1672-1736) - Kim, Sun Joo, 1962- (Stanford University Press, 2013)
Kim resurrects the forgotten historical memory of people, family, lineage, and region, while at the same time enriching the social history of late Choson Korea, by examining the life and work of Yi Sihang, a historically obscure person from a hinterland in the northwestern region, but an advocate of the history and culture of the region he came from and a literatus whose literary talent was recognised by his contemporaries.